2021
DOI: 10.1111/ijfs.15034
|View full text |Cite
|
Sign up to set email alerts
|

Determination of phenolic antioxidants in tuna fillets canned in hydrosols with HPLC‐DAD

Abstract: Canned tuna was fortified with a mixture of brine and hydrosols of aromatic plants (i.e. oregano, laurel, sage and lemon balm). An HPLC-DAD method was developed and validated for the simultaneous determination of thirteen antioxidants in tuna fillets, including phenolic acids (gallic acid, vanillic acid, syringic acid and rosmarinic acid), flavonoids (catechin, epicatechin, vanillin, myricetin, rutin, quercetin, luteolin and apigenin) and one hydroxybenzaldehyde (syringaldehyde). The analytes showed satisfying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…The ORAC analysis demonstrated the ability of the plant extract to generate reactions involving hydrogen atom transfer; likewise, the analysis suggested that the antioxidant response was mainly associated with polar compounds, among them, the compound rutin present in the calyx of goldenberry. This component has demonstrated antioxidant efficacy through the transfer of hydrogen atoms, which limits lipid peroxidation generated by peroxyl radicals in a large number of biological processes (Kalogiouri et al, 2021).…”
Section: Optimisation Of the Antioxidant Capacitymentioning
confidence: 99%
“…The ORAC analysis demonstrated the ability of the plant extract to generate reactions involving hydrogen atom transfer; likewise, the analysis suggested that the antioxidant response was mainly associated with polar compounds, among them, the compound rutin present in the calyx of goldenberry. This component has demonstrated antioxidant efficacy through the transfer of hydrogen atoms, which limits lipid peroxidation generated by peroxyl radicals in a large number of biological processes (Kalogiouri et al, 2021).…”
Section: Optimisation Of the Antioxidant Capacitymentioning
confidence: 99%